Perceptions and Responses of Diversified Farm Producers in the Northern Great Plains to the Early Stage of the COVID-19 Pandemic - Ebel, Roland; Ahmed, Selena; Warne, Teresa; Moxley, Alexandria; Grimberg, Irene; Jarchow, Meghann; Menalled, Fabian D. (Frontiers in Sustainable Food Systems, 2022)
The initial months of the COVID-19 pandemic revealed unique vulnerabilities of the global food system with notable societal consequences, calling for the need to implement resilience strategies to support food security for all. The objective of this study was to elicit perceptions, experiences, and responses of producers of diversified farms in the Northern Great Plains of the United States to the early stage of the COVID-19 pandemic towards identifying factors for strengthening the resilience of agricultural production for supporting livelihoods and food security. Between May and August 2020, a cross-sectional online survey was administered to the emerging community of diversified farm managers in two rural U.S. states, Montana and South Dakota (n=53), where monocropping and extensive livestock production are prevalent. About two-thirds of surveyed producers (68%) reported that they did not change their farming practices in response to the pandemic up until the survey period in Summer 2020. Almost three-quarters of producers (73%) indicated that access to commodities, farm inputs, and farm labor was not a concern for them during the early stage of the pandemic. Most surveyed producers (88%) were not concerned about their household food security and expressed confidence regarding a long-term increase in the demand for local food. However, almost half of surveyed producers (47%) reported that their anxiety increased because of the pandemic. Findings further highlight that small farms implemented a greater number of practices for enhancing ecological self-regulation while depending strongly on off-farm income compared to larger farms that were economically more autonomous. This study points to the promise of farm system diversification in strengthening the resilience of agricultural systems. We conclude by outlining pathways for increasing diversity on farms towards supporting food security during extreme food system shocks.